2019
DOI: 10.1002/ece3.5497
|View full text |Cite
|
Sign up to set email alerts
|

Conspecific olfactory preferences and interspecific divergence in odor cues in a chickadee hybrid zone

Abstract: Understanding how mating cues promote reproductive isolation upon secondary contact is important in describing the speciation process in animals. Divergent chemical cues have been shown to act in reproductive isolation across many animal taxa. However, such cues have been overlooked in avian speciation, particularly in passerines, in favor of more traditional signals such as song and plumage. Here, we aim to test the potential for odor to act as a mate choice cue, and therefore contribute to premating reproduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 127 publications
(217 reference statements)
0
12
0
Order By: Relevance
“…Most of the studies included in our comparative analysis did not test birds’ ability to discriminate between the sexes, but evidence for sex discrimination was found in all six of the studies that did (Zhang et al ., 2010; Whittaker et al ., 2011a; Amo et al ., 2012; Mihailova, 2014; Grieves et al ., 2019a; Van Huynh & Rice, 2019). In breeding‐condition Passeriformes, both sexes spent more time with male odour in dark‐eyed juncos (Whittaker et al ., 2011a) and spotless starlings ( Sturnus unicolor ; Amo et al ., 2012).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Most of the studies included in our comparative analysis did not test birds’ ability to discriminate between the sexes, but evidence for sex discrimination was found in all six of the studies that did (Zhang et al ., 2010; Whittaker et al ., 2011a; Amo et al ., 2012; Mihailova, 2014; Grieves et al ., 2019a; Van Huynh & Rice, 2019). In breeding‐condition Passeriformes, both sexes spent more time with male odour in dark‐eyed juncos (Whittaker et al ., 2011a) and spotless starlings ( Sturnus unicolor ; Amo et al ., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In breeding‐condition Passeriformes, both sexes spent more time with male odour in dark‐eyed juncos (Whittaker et al ., 2011a) and spotless starlings ( Sturnus unicolor ; Amo et al ., 2012). By contrast, both sexes spent more time with opposite sex odour in black‐capped chickadees ( Poecile atricapillus ), Carolina chickadees ( Poecile carolinensis ; Van Huynh & Rice, 2019), and song sparrows (Grieves et al ., 2019a). In Psittaciformes, female budgerigars ( Melopsittacus undulatus ) spent more time with male odour (Zhang et al ., 2010), and female crimson rosellas ( Platycercus elegans ) spent more time on nest boxes treated with male odour than female odour (Mihailova, 2014), suggesting a preference for these odour types.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, much recent behavioral work has demonstrated that birds use odor in many important ecological contexts, such as in mate choice and species recognition (Bonadonna and Mardon 2013, Zhang et al 2013, Van Huynh and Rice 2019, kin recognition (Fracasso et al 2019), predator avoidance (Amo et al 2008, Roth et al 2008, Stanbury and Briskie 2015, Lee 2021, nesting (Petit et al 2002, Gwinner and Berger 2008, Shutler 2019, foraging (Hutchinson and Wenzel 1980, Hiltpold and Shriver 2018, Saavedra and Amo 2018a, Potier et al 2019, Potier 2020, and navigation (Pollonara et al 2015, Abolaffio et al 2018, Zannoni et al 2020. Here, we assess the ability for birds to cue in on plant volatiles to locate insect prey.…”
Section: Introductionmentioning
confidence: 99%